2017
DOI: 10.18203/2394-6040.ijcmph20172150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga on general health: food habits versus blood groups

Abstract: INTRODUCTIONThe medical fraternity and scientists across the globe have not subscribed concretely the blood group relation with food habits. Here in this article, we are critically analyzing its relationship with calories intake. This critical study throws many challenges to the experts in the field of nutrition, dieticians, naturopathy therapists, and other such health practitioners.The prevalent concepts of diet and nutrition are based on age, calorie requirements, sex, and nature of work of a person. A diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These items are tested with fifty different blood group participants as given in Table 2. In our previous sample study of 50 cases (Acharya et al 2017) it was shown that 4 major blood groups have almost the same food habits in term of calorie intake. At present also we have considered the same group of 50 persons and carried out the studies with yoga wellness card and with OOFH shown in Table 6.…”
Section: Resultsmentioning
confidence: 92%
“…These items are tested with fifty different blood group participants as given in Table 2. In our previous sample study of 50 cases (Acharya et al 2017) it was shown that 4 major blood groups have almost the same food habits in term of calorie intake. At present also we have considered the same group of 50 persons and carried out the studies with yoga wellness card and with OOFH shown in Table 6.…”
Section: Resultsmentioning
confidence: 92%